Fish communities of Paya Bungor, with notes on its development, management and recreational use - Mohd. Azmi Ambak (Fakulti Pengajian Maritim dan Sains Marin, 2011)
Paya Bungor Lake is presently being developed into a recreational area by Pahang State Economic Planning Unit. As a contribution to provide a basis to ensure its sound development and management, an 18 month field study was conducted. This thesis presents (a) the general description of the limnological and other ecological properties of Paya Bungor, (b) the analysis of the fish populations including species composition, abundance, distribution patterns, community structure and the population dynamics of the major species, and (c) proposals for the management of Paya Bungor with emphasis on recreational fisheries.